The Companions We Keep: A Situational Analysis and Proposed Typology of Companion Animal Cruelty Offenses. Issue 9 (2nd September 2018) - Grugan, Shannon T.
ABSTRACT: Abuse and neglect of non-human companion animals (i.e., pets) are not well understood as crime phenomena even though the keeping of animals as companions is relatively commonplace, reports of abuse and neglect are not at all rare, and the media generally serves to reinforce this notion that cruelty is a frequently occurring and widespread problem. This study is a content analysis of 179 cases of companion animal cruelty featured in news media reported in the United States during the first six months of 2013. Typological analysis led to the identification of various patterns and themes in terms of actors involved and other situational factors contributing to cruelty events, resulting in the identification of the categories of companion animal cruelty offenses. The implications of this typology are discussed in terms of: (1) existing theoretical framework of cruelty, violence, and opportunity and (2) expansion of understanding of animal cruelty based on newly identified features of cruelty events.